Economic study about termination in fed Guzera cattle containment levels with diets containing concentrate growing - Estremote, Marcelo [UNESP]; Bonilha Pinheiro, Rafael Silvio [UNESP]; Neto, Marcos Chiquitelli [UNESP]; Sabbag, Omar Jorge [UNESP]; Homem Junior, Antonio Carlos (Univ Fed Rural Pernambuco, Dept Administracao, 2017)
The work involved an economic and financial study to evaluate the costs and profitability of Guzera cattle feedlot fed with increasing levels of concentrate diets with 30%, 50% or 70% of concentrate. Data were collected in an experimental feedlot located in the county of Ilha Solteira-SP, were used 36 cattle race Guzera uncastrated, aged 30 months and weighing 464 kg, the animals form kept in individual stalls, and fed twice a day for a period of 56 days without interrupted treatment. The experimental design was completely randomized, with three treatments and twelve repetitions. The diet containing 30% concentrate had the lowest variable cost (R$254.24 per animal) and the smallest margin, getting to R$43.60/animal deficit. The best economic result was obtained with the diet 50% concentrate with a gain of R$18.47/animal. Considering the importance of food in animal's confinement, efficient cost management is a key issue for its profitability.
Keywords: Costs; Profitability; Cattle; Management